2005
DOI: 10.1037/0022-006x.73.2.300
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Partner Reactions to Diagnosis and Treatment of Breast Cancer: Impact on Psychosocial and Psychosexual Adjustment.

Abstract: Two studies examined breast cancer patients' perceptions of their partners' reactions to their diagnosis and treatment as influences on 3 aspects of patients' well-being: psychosexual adjustment, emotional distress, and marital satisfaction. Study 1, cross-sectional, indicated that partner initiation of sex, frequency of sex, a positive 1st sexual experience after treatment, and especially perception of the partner's emotional involvement in the relationship, were relevant to these outcomes. Study 2, longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(97 citation statements)
references
References 68 publications
8
78
0
11
Order By: Relevance
“…Using the same measure of psychosexual well-being, Wimberly, Carver, Laurenceau, Harris and Antoni (2005) found that this variable correlated an average of 0.74 across adjacent measurements, consistent with the present findings. A study of prospective relationships between social support, distress, and life disruption among breast cancer patients found that perceived social support from partners (using a different measure) changed from pre-to post-surgery and then remained relatively stable throughout the following year .…”
Section: Discussionsupporting
confidence: 81%
“…Using the same measure of psychosexual well-being, Wimberly, Carver, Laurenceau, Harris and Antoni (2005) found that this variable correlated an average of 0.74 across adjacent measurements, consistent with the present findings. A study of prospective relationships between social support, distress, and life disruption among breast cancer patients found that perceived social support from partners (using a different measure) changed from pre-to post-surgery and then remained relatively stable throughout the following year .…”
Section: Discussionsupporting
confidence: 81%
“…We noted that single women with breast cancer scored higher on the interpersonal sensitivity symptom, which suggest that they may be more susceptible to problems relating to appropriately understanding others and responding accordingly. Husband is an important source of family support and his emotional involvement and understanding of the spouse's cancer experience is directly associated with psychological adjustment and outcomes (Wimberly et al, 2005;Manne et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sexuality and intimacy can reduce emotional distress and improve psychosocial response to cancer diagnosis and complications following treatment. 16,17 However, discussion of sexual functioning has long been a subject of taboo in the healthcare system. Thus, sexual functioning is one QOL variable, in particular, that needs further research, and it is necessary to draw attention to the impact that HSCT has on the sexuality and sexual functioning in patients after HSCT.…”
Section: Introductionmentioning
confidence: 99%